Efektivitas Hot Stone Massage Pada Penderita Low Back Pain (LBP) : Literature Review - Bayu Febrianto; Nyimas Najwa Putri Rahayu Khairunnisa; Afifah Jasmine Yohan Putri; Dini Nur Alpiah (LPPM STIKES KESETIAKAWANAN SOSIAL INDONESIA, 2023)
Low Back Pain (LBP) has long been recognized as the only musculoskeletal condition that adversely affects more than three adults in daily life, known as the second skeletal ganglion. Hot Stone Massage uses bones that have been trained to be used as a means of relaxing muscles, ligaments and tendons. Objective: to determine the effectiveness of Hot Stone Massage in reducing pain in LBP sufferers. The research method used is a literature review approach, by searching for references using the PICO method on the Google Scholar database over a period of 10 years. Results: From the 3 journals studied, Hot Stone Massage had an effect on reducing pain in patients suffering from LBP, with temperature intensity >38°C and p-value p<0.05 showing a significant effect. Conclusion: The use of hot stone therapy also reduces the amount of pain that interferes with daily activities, such as the ability to manage loads, work performance, and sleep quality, in addition to providing long-lasting pain protection for most users during use and for two weeks after use.